1997
DOI: 10.1590/s0004-282x1997000500009
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogênio como fator de risco independente de doença vascular cerebral

Abstract: RESUMO -No protocolo de avaliação clínico-laboratorial de pacientes com acidente vascular cerebral (AVC) aterotrombótico dosamos e analisamos níveis de fibrinogênio plasmático (técnica de Clauss automatizada), para determinar seu possível papel como fator de risco trombogênico em 29 pacientes (20 homens e 9 mulheres) com idades entre 25 a 79 anos (mediana=55); todos tinham tido AVC aterotrombótico. Eles foram classificados em 2 grupos segundo alterações de fluxo nas carótidas: g1 -sem alteração de fluxo (n=19)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Fukujima et al . found that FDP participate the development and progression of atherosclerosis and thrombus30. Corban MT et al .…”
Section: Discussionmentioning
confidence: 96%
“…Fukujima et al . found that FDP participate the development and progression of atherosclerosis and thrombus30. Corban MT et al .…”
Section: Discussionmentioning
confidence: 96%
“…Epidemiological studies have demonstrated that hyperfibrinogenemia is an independent risk factor for stroke, as well as that fibrinogen (Fg), fibrin (Fb), and fibrinogen degradation products (FDPs) are involved in the formation and development of atherosclerosis (AS) [1, 2]. Fg is a 340 kD glycoprotein which is constitutively expressed exclusively in hepatocytes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding fibrinogen, its main function relates to blood coagulation. Excess of fibrinogen in the intimal layer of the cerebral vessels may lead to thickening and subsequent accumulation of atherosclerotic plaque, and, consequently, impairment of different domains of cognition 28 . In relation to self-reported health status, the results from multivariate analyses in the present study indicated that there was an independent association with the outcome and a significant linear trend for prevalence ratios (p , 0.01).…”
Section: Discussionmentioning
confidence: 99%